Study of relationship between Platelet Volume Indices and Hyperlipidemia - Khemka, Rashi; Kulkarni, Kalpana (Annals of Pathology and Laboratory Medicine, 2014)
Background: Mean platelet volume (MPV) correlates well with platelet activity as larger platelets tend to be metabolically and enzymatically more active than smaller platelets and secrete more prothrombotic factors. Studies have shown that there is a constant association of increased MPV with atherosclerotic diseases like coronary ischemic disease, myocardial infarction and cerebral infarct as well as with diabetes and hypertension. Hyperlipidemia, being a closely associated condition, is also expected to show changes in platelet size. We try to study the relationship between platelet volume indices and hyperlipidemia. Methods:Â 100 patients with deranged lipid profile on recent lab biochemical lab reports in OPD and indoor ward patients of Sassoon general hospital, Pune have been studied. Included cases have been segregated as separate groups for patients with deranged lipid profile along with atherosclerotic disease, diabetes or hypertension.Â The platelet parameters like platelet count and the platelet volume indices (PVI), including mean platelet volume (MPV), platelet distribution width (PDW), and platelet large cell ratio (Pâ€LCR); were compared with 30 age matched controls. Results: Mean MPV (9.79 Â±1.01), PDW (13.18 Â± 2.44) and P-LCR (24.85 Â± 7.14) of cases were significantly higher than the controls (mean MPV = 9.22 Â± 0.91, mean PDW= 11.64 Â± 1.75, mean P-LCR= 20.70 Â± 7.07; p-value < 0.05). Also, hyperlipidemic patients having an associated disease had significantly higher PVI than the patients having hyperlipidemia in isolation. Conclusion: The estimation of these indices can be considered as an early, economical and rapid procedure for identification of complications in hyperlipidemic patients. Â